2014
DOI: 10.4103/0972-124x.147409
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of salivary soluble CD44 levels in periodontal health and disease

Abstract: Context:Inflammation, immunoactivation, and malignant diseases are associated with increased plasma levels of soluble CD44 (sCD44). Serum sCD44 has been recognized as a diagnostic marker in smoking-induced diseases.Aim:(1) To assess the levels of salivary sCD44 in periodontal health and disease. (2) To compare the levels of salivary sCD44 in smokers and nonsmokers. (3) To assess if salivary sCD44 levels could be used as a diagnostic marker for periodontitis.Setting and Design:A total of 60 patients were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…A total of 2,763 studies were identified from Medline and Scopus, and 1,934 studies remained after removing duplicates. Of these, 1,878 studies were ineligible for reasons described in Figure , leaving 56 that were eligible for review. Six studies were excluded because of insufficient data after contacting the authors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 2,763 studies were identified from Medline and Scopus, and 1,934 studies remained after removing duplicates. Of these, 1,878 studies were ineligible for reasons described in Figure , leaving 56 that were eligible for review. Six studies were excluded because of insufficient data after contacting the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 50 studies, 45 objectively assessed OH using an oral examination. Of these 45 studies, 15 analysed OH as categorical data, 31 as continuous data and one as both. Eleven studies provided the association between periodontitis and oral care habits measured according to the frequency of brushing, interdental cleaning and dental visits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 However, sCD44 levels increased in the acute phase of Trypanosoma cruzi infection compared to healthy controls, but levels decreased in the chronic phase with advanced cardiopathy compared to healthy controls and patients with milder disease. 90 Recently, it was observed that sCD44 increases in hepatic steatosis 91 and chronic and aggressive periodontal disease, 92 and its levels correlate with the evolution of endometriosis. 93 One study analyzed sEpCAM in endometriosis, and did not find any correlation.…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…Only a single report of this surface antigen in periodontitis, where it was shown to be increased on both epithelial cells and polymorphonuclear neutrophils collected from the gingival crevice and was related to the severity of the disease . CD44 is involved in lymphocyte activation, recirculation and homing, and has been identified at the cellular level and in saliva related to periodontitis . CD46 acts as a cofactor for complement factor I, acts as a costimulatory factor for T cells to induce differentiation of CD4 + cells that can suppress immune responses through secretion of IL‐10.…”
Section: Discussionmentioning
confidence: 99%